PENGARUH IKLIM BELAJAR DAN MINAT BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIKA DIMASA PANDEMIK SISWA KELAS V SEKOLAH DASAR SE KECAMATAN MALILI - Didik Setiawan (Universitas Muhammadiyah Makassar, 2021)
The existence of the COVID-19 pandemic that hit our country greatly affected the world of education, the change in the learning process from face to face to online resulted in a change in the learning atmosphere for students, as well as student interest in learning. This change in the learning process of course resulted in students' understanding of mathematical concepts being also affected.This study aims to determine the description of the learning climate, interest in learning, and understanding of mathematical concepts for fifth grade elementary school students in Malili District during the Covid-19 pandemic both simultaneously and simultaneously. partially. This type of research is ex-post facto. In this study, the population was all fifth grade elementary school students in Malili District, with a sample of 80 people by random sampling. Data on learning climate and interest in learning were obtained using a questionnaire and mathematics learning outcomes using tests. Analysis of the data used is descriptive analysis to describe the characteristics of each variable and inferential analysis to test the research hypothesis used regression test. The results showed that the learning climate of elementary school students V in Malili District was in the low category, interest in learning was in the high category, while understanding of mathematical concepts was in the high category. There is an influence of learning climate on students' understanding of mathematical concepts, there is an influence of interest in learning on students' understanding of mathematical concepts and there is an influence of learning climate and interest in learning on students' understanding of mathematical concepts. This research provides information for educators regarding the influence of learning climate and interest in learning on students' understanding of mathematical concepts and becomes a reference for further researchers